2013
DOI: 10.1007/s11011-013-9396-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility of brain acetylcholinesterase activity to methylmalonate in young rats with renal failure

Abstract: Tissue methylmalonic acid (MMA) accumulation is the biochemical hallmark of methylmalonic acidemia. Clinically, the disease is characterized by progressive neurological deterioration and renal failure, whose pathophysiology is still undefined. In the present study we investigated the effect of acute MMA administration on some important parameters of brain neurotransmission in cerebral cortex of rats, namely Na(+), K(+)-ATPase, ouabain-insensitive ATPases and acetylcholinesterase activities, in the presence or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Neurological complications remain a major concern, partly related to MMlevels . All additional risk factors, such as drugs, high blood pressure, hydroelectrolytic disorders, should be strictly screened and controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Neurological complications remain a major concern, partly related to MMlevels . All additional risk factors, such as drugs, high blood pressure, hydroelectrolytic disorders, should be strictly screened and controlled.…”
Section: Discussionmentioning
confidence: 99%
“…There was a significant elevation in AchE levels observed in tMCAO-only animals, and these were lowered with P4 administration. Studies have reported that AchE activity is increased by oxygen and nitrogen reactive species (Affonso et al, 2013). Considering that increased AchE activity has been related to progressive neurological decline and neurodegenerative diseases such as Alzheimer's and Parkinson's disease, it is presumed that a disruption in the cholinergic system may be involved in the neurological deficit associated with the tMCAO model of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of the metabolic imbalance observed in Tbx1 +/- mice on brain health is unknown, but the presence of toxic metabolites such as MMA might affect brain function (Ribeiro et al, 2013)(Affonso et al, 2013). We therefore tested whether vB12 treatment was able to rescue the sensorimotor gating deficit (reduced pre-pulse inhibition, PPI) that we have reported (Paylor et al, 2006).…”
Section: Resultsmentioning
confidence: 99%